The potential that ethical finance has to generate new investment alternatives in Colombia (2008)
This article examines the need for and the opportunity of developing ethical finance initiatives, specifically ethical banks and ethical investment funds, as alternatives to strengthen development in Colombia. The validity of such alternatives La is justified through the empirical verification of economic inequality, the limited depth of the traditional financial system, the lack of appropriate investment alternatives to the socioeconomic structure in this country, and the interest of the persons who will potentially acquire the proposed services. The last aspect is based on an analysis of the information obtained from a survey made in Bogotá to 350 persons. The proposals are justified by the available evidence regarding the limitations that the Colombian financial system has and the interest of the potential users of ethical finance initiatives. Likewise, this article proposes an in-depth study of the real possibilities and expected impacts of the proponed initiatives and the effective de involvement of interested social and economic stakeholders. Finally, it suggests several reflections for development in an immediate future to take into account the elements that are relevant to the Colombian context.